Pengaruh Kecemasan Matematika terhadap Prestasi Belajar Matematika Siswa SMP Negeri 2 Jogoroto - Maf'ulah, Syarifatul; Fadhilah, Fadhilah (Postulat : Jurnal Inovasi Pendidikan Matematika, 2024)
Students' mathematics learning achievement is influenced by several factors, one of which is anxiety. The purpose of this study was to determine whether or not there is an effect of mathematics anxiety on students' mathematics learning achievement. This study is a correlational study. The population in this study were all students of class VIII of SMP Negeri 2 Jogoroto in the 2021/2022 academic year consisting of 160 students. The sampling technique in this study used a random sampling technique, namely a random sampling technique. The number of samples in the study was 40 students. Data collection used two methods, namely the questionnaire method and the documentation method. The research instrument used a questionnaire sheet and a documentation sheet. The validity of the instrument used expert validity. Data analysis used simple linear regression analysis. The results of the data analysis obtained a Sig value of 0.000 <0.05 so that H_0 was rejected, meaning that there is an effect of mathematics anxiety on students' mathematics learning achievement at SMP Negeri 2 Jogoroto with a regression equation Y = 94.614-0.739, which means that for every 1 increase in the score obtained in mathematics anxiety, learning achievement will decrease by 0.739. The magnitude of the correlation is -0.822 with a Sig value of 0.000 <0.05 so that H_0 is rejected, meaning that there is a significant relationship between mathematics anxiety and students' mathematics learning achievement at SMP Negeri 2 Jogoroto. With a Determination Coefficient value of 0.676, it shows that there is an influence of mathematics anxiety of 67.6% and 32.4% is influenced by other factors that are not studied.